Coherence invariant mappings on block triangular matrix spaces - Chooi, W (2002)
n this paper we classify bijective mappings psi on the space of block Lipper triangular matrices such that both psi and psi(-1) preserve pairs of matrices whose differences have rank one. Applications to rank one preservers and semi-isomorphisms are considered. (C) 2002 Elsevier Science Inc. All rights reserved.